On The Job Training Effectiveness And Employee Performance: A Case Study Of Public Agency In Sibu, Sarawak. - Charles, Christopher (Universiti Malaysia Sarawak (UNIMAS), 2020)
The purpose of this study is to identify on the job training effectiveness and employee performance of public agency in Sibu, Sarawak. Previous research indicates that on the job training could distant leads to employee performance. Kirkpatrick model and Expectancy theory is used in this study. The on the job training is acquired through the process of reactions, learning, transfer and results and the employee motivation will be observed in their performance. This study is using qualitative methodology and has been conducted at employees in Rajang Port Authority in Sibu, Sarawak. A set of interview questions is used as research instrument in this study. The data was collected based on interview of 5 informants in this organization. All the data collection has been analyzed and discussed by the researchers. The findings show that the employee was actively engaged in training based on their understanding of the on the job training. The factor that contribute to on the job training effectiveness has been discuss and majority of informants agree that those factors would affect to employee performance. The on the job implementation has been explore which is the training method such as sharing session, lecture session, practical session, slide presentation session and role play session. The few issues that affect the on the job effectiveness has been discussed by the informants. Thus, from the findings that has been analyzed, the suggestion and recommendations were made to the organization, top management and the future researchers. The recommendations were made to improve the on the job training design and maximize the performance of employees to the workplace.